Pelatihan TOEFL Online untuk mahasiswa semester 4 di masa PPKM 2021 - Lina, Marisa Fran (Penamas: Journal of Community Service, 2022)
One of the English proficiency tests is TOEFL (Test Of English as a Foreign Language) which is increasingly being used for various purposes. This community service article is based on the TOEFL Online Training for students in Salatiga to equip 25 fourth-semester students who already have background knowledge of Basic English in the previous semester. This training was carried out online through Google Meet, Google Classroom and WhatsApp Group in August 2021 due to PPKM (Restrictions on Community Activities). This activity was held for 20 meetings, starting with an online pre-test and ending with an online post-test. The training per meeting lasted 120 minutes, namely: conducting pre-teaching activities, presenting material according to topics per meeting, asking and answering questions, practicing the theories/strategies taught by doing exercises, and providing direct feedback/evaluations to students. At the end of the activity, participants who meet the requirements will be given 2 certificates of participation and also a certificate of TOEFL test results. From these activities, it can be concluded that TOEFL is very important for students to equip them with recognized English skills for academic purposes. Tes kecakapan Bahasa Inggris salah satunya adalah TOEFL (Test Of English as a Foreign Language) yang semakin luas digunakan untuk berbagai kepentingan. Artikel Pengabdian ini disusun berdasarkan pelatihan online TOEFL untuk mahasiswa di Salatiga untuk membekali 25 mahasiswa semester 4 yang sudah memiliki background pengetahuan Bahasa Inggris dasar di semester sebelumnya. Pelatihan ini dilaksanakan secara online melalui Google Meet, Google Classroom dan WhatsApp Group pada bulan Agustus-September 2021 karena adanya PPKM (Pemberlakuan Pembatasan Kegiatan Masyarakat). Kegiatan ini terselenggara sebanyak 20 pertemuan, diawali dengan pre-test online lalu diakhiri dengan post-test online. Adapun kegiatan pelatihannya per pertemuan berdurasi 120 menit, yaitu: melakukan kegiatan pra-pengajaran, pemaparan materi sesuai pembagian topik per meeting, tanya jawab, mempraktikkan teori/strategi yang diajarkan dengan mengerjakan soal-soal latihan, dan pemberian feedback/evaluasi langsung kepada mahasiswa. Di akhir kegiatan, para peserta yang memenuhi syarat akan diberikan 2 sertifikat keikutsertaan pelatihan dan juga sertifikat hasil tes TOEFL Dari kegiatan tersebut dapat ditarik kesimpulan bahwa pelatihan TOEFL sangat penting bagi mahasiswa untuk membekali mereka keterampilan Bahasa Inggris yang diakui untuk keperluan akademik mereka.